Afrofuturism as critical constructionist design: building futures from the past and present. Issue 4 (1st October 2020) - Holbert, Nathan; Dando, Michael; Correa, Isabel
ABSTRACT: Society's ability to collectively address global challenges will require efforts to include diverse voices, perspectives, and epistemologies. Building on critical design, which positions these challenges as requiring changes in our values and beliefs, we examine the nature and potential of a critical constructionist design framework within an Afrofuturist aesthetic. This framework invites Black youth to critically examine social, economic, and environmental systems by both connecting to personal and family histories as well as reflecting on local and lived experiences. We ground our discussion of this framework in an implementation where, in consultation with professional designers, artists, and scholars, five Black teen girls designed and produced a collection of critical artifacts. We invited participants to use their personal experiences in the present, as well as their family and cultural histories, to design futuristic artifacts that critique existing social inequities and environmental instability.